PROPOSTAS DE DIRETRIZES PARA A GESTÃO DE SMS NO MANUSEIO DE PROPILENO GLICOL DINITRATO EM PLANTAS INDUSTRIAIS - Guimaraes, Francisco Carlos Pereira (2012)
Management systems have been shown to be increasingly present in organizations. The quest for excellence in Health, Safety and Environmental Management System (HSE), has become a strategic goal for companies that wish to participate in an increasingly competitive market. One of the initiatives of most of these companies in HSE management is to adapt the workplace in the execution of their duties. This study presents aspects related to occupational exposure to 1,2-propylene glycol dinitrate, as well as recommendations for its handling. The methodology used is based on literature review and in the preparation and implementation of a questionnaire to 12 experts in order to assess the proposed guidelines. On the basis of the results, it was possible to conclude that the occupational concerns related guidelines, the working environment, handling, storage and exposure to 1,2-propylene glycol dinitrate can minimize the risks to workers and the environment. The proposed guidelines contribute in field theory and practice for the management of health, safety and environment (HSE) in the handling of chemical industrial plants.